2019
DOI: 10.3233/jad-180859
|View full text |Cite
|
Sign up to set email alerts
|

APOE ɛ4 Gene Dose and Sex Effects on Alzheimer’s Disease MRI Biomarkers in Older Adults with Mild Cognitive Impairment

Abstract: Background: APOE 4 and sex have been linked to increased risk for conversion to Alzheimer's disease (AD). However, the relationship between APOE 4 gene dose, sex, and AD biomarkers remains understudied. Objective: To investigate the effect of APOE 4 dose on AD biomarkers in a sample of older adults with mild cognitive impairment (MCI), and to examine whether APOE 4 dose modifies AD risk differently in MCI women and men. Methods: We examined cross-sectional AD biomarkers for participants with MCI (n = 930, 55-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…Interestingly, there are also sex differences in the effects of apolipoprotein E allele 4 (APOE4), the predominant genetic risk factor for late-onset AD [27]. Deleterious APOE4associated outcomes, including risk for AD [28][29][30], conversion from normal cognition to mild cognitive impairment [29][30][31] and even pathology in rodent models of AD [32,33] are typically reported to be higher in females than in males.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there are also sex differences in the effects of apolipoprotein E allele 4 (APOE4), the predominant genetic risk factor for late-onset AD [27]. Deleterious APOE4associated outcomes, including risk for AD [28][29][30], conversion from normal cognition to mild cognitive impairment [29][30][31] and even pathology in rodent models of AD [32,33] are typically reported to be higher in females than in males.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent study indicates that APOE4 may affect cognition more strongly in women than men. 10 Further studies validating whether BBB dysfunction in APOE4 carriers is correlated with aging or affected by sex should be important in order to truly understand the neurovascular pathobiology of cognitive impairment.…”
mentioning
confidence: 99%
“…Recent metabolic and transcriptomic data add potential mechanistic explanations to the findings of this study 34 - 37 . For example, prior work has found that specific metabolic effects were limited to FACs.…”
Section: Discussionmentioning
confidence: 55%